The East Asian Crisis and Philippine Sustainable Development - Erlinda M. Medalla; Ponciano Jr. S. Intal (Philippine Institute for Development Studies (PIDS), 1998)
Asia is not only the most polluted and environmentally degraded region in the world, but it also houses the most number of poor households. Hence, the magnitude of the financial and economic crisis can be expected to have an impact in the region's sustainable development prospects, the nature and the period of which are likely to be determined by the state of the country's environment and social development. In particular, the paper looks into the impact of East Asian crisis into the Philippine economy at the time when the country itself has the El Nino to deal with. It also highlights the implications of the crisis and the El Nino on various policy and institutional challenges in the areas of water resources, upland and coastal areas and the urban environment.
Keywords: 330; Asian financial crisis; El Ni\~no phenomenon